Extraction, Chemical Composition and Antimicrobial Activity of the Essential Oils of Pipilongo (Piper Tuberculatum)Using Supercritical Carbon Dioxide - Restrepo Osorio, Jaime; Colmenares Dulcey, Ana Julia; Mora, Luis E.; Sánchez Andica, Rubén Albeiro (Revista de Ciencias, 2013)
Essential oils from pipilongo seeds (Piper tuberculatum) was extracted using supercritical carbon dioxide. The extraction was performed as a function of particle size of the grinded seeds. The highest yield (2,812%) was obtained with the smallest particle size. The chemical composition analysis of the oil by GC-MS led to identify 15 compounds, some of which are β-elemene, caryophyllene, β-farnesene, neophytadiene and piperine among others. The microbicide activity of the essential oil was determined by Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) assays, showing that the growth of the bacteria Staphylococcus aureus and Bacillus subtilis was inhibited, and hence with a possible microbicidal effect, whereas for pseudomonas aeruginosa and Salmonella typhimurium showed no effect on their growth.